Closed kinetic chain (CKC) Exercise In Knee Joint Rehabilitation: A Narrative Review - Arista, I Gede Peri; Yasa, I Made Astika (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Musculoskeletal disorders of the knee joint are common health problems that can cause pain, decreased physical function, and limitations in daily activities. This study aimed to synthesize scientific evidence on the effectiveness of closed kinetic chain exercises on pain, physical function, balance, and mobility in musculoskeletal disorders, particularly in the knee joint. This study used a narrative review approach. Articles were obtained from the Scopus database within the 2020–2025 period using relevant keywords. The selection process was conducted based on PRISMA guidelines with predetermined inclusion and exclusion criteria, resulting in five eligible articles for further analysis. The methodological quality of the studies was assessed using the PEDro scale. The results show that closed kinetic chain exercises provide benefits in musculoskeletal rehabilitation, especially in knee joint disorders. These exercises reduce pain, improve muscle strength, enhance balance and postural stability, and increase physical function and mobility. The discussion indicates that these exercises support functional movement patterns and coordinated muscle activation, making them effective in improving joint stability. In conclusion, closed kinetic chain exercises are an effective intervention for musculoskeletal rehabilitation in knee joint disorders as they improve joint stability, muscle strength, and functional movement.